Utilização de técnicas projetuais e construtivas de baixo impacto ambiental: estudo de caso em edificação unifamiliar - Valvassori, Letícia Hatamoto (Universidade Federal de São Carlos, 2021)
ABSTRACT The civil construction sector has been responsible for significant environmental degradation, either by the consumption of natural resources, or by the production of a critical volume of waste and pollution. In the global context, minimize these impacts is part of the efforts to allow future generations to meet their demands. Knowing that the environmental impacts of a building extend throughout its life cycle, the solutions adopted in the conception and design phases have high potential to reduce or increase it. From this perspective, this paper was structured in two parts. The first one was a bibliographic review to survey and compile procedures, measures, and solutions with low environmental impact for single-family homes. This investigation was guided by topics related to water, human environmental comfort, and energy, and also includes the environmental certifications, approaching, more specifically, the seal Selo Casa Azul and the label Qualiverde. In the second part, based on the subsidies obtained, a case study of a residence located in São Carlos, which sought to implement solutions aligned to a more sustainable perspective, was carried out. Thus, along with the systematization of these design and constructive solutions, it was possible to analyze how the case study absorbed and incorporated the solutions with low environmental impact, discussing relevant aspects. The characteristics of this plot, such as its area of 5,000m², enabled the adoption of a set of solutions that could hardly be used in dense urban areas. On the other hand, within the analyzed variables, some of the solutions used could be improved. In this discussion, it is emphasized that sustainability doesn’t have an achievable limit. In the end, the importance of considering a set of solutions aimed at sustainability and adequate for each context, from the initial design stage, is highlighted, so that it can complement each other and efficiently promote the reduction or, if possible, elimination of different types of impacts.
Use of low environmental impact design and construction techniques: a case study in a single-family building
Keywords: Soluções construtivas sustentáveis; Certificação ambiental; Impactos ambientais da construção civil; Sustainable building solutions; Environmental certification; Environmental impacts of civil construction; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL::INSTALACOES PREDIAIS; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL::MATERIAIS E COMPONENTES DE CONSTRUCAO; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL::PROCESSOS CONSTRUTIVOS; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PROJETO DE ARQUITETUTA E URBANISMO::PLANEJAMENTO E PROJETOS DA EDIFICACAO